Systematics of the genus Tylolaimophorus de Man, 1880 (Nematoda: Diphtherophoridae), with description of T. minor (Thorne, 1939) Goodey, 1963 from Iran - Ghaderi, Reza; Asghari, Ramezan; Eskandari, Ali (Zootaxa, 2020)
The present work is a compilation of the systematics of the genus Tylolaimophorus (Nematoda: Diphtherophoridae). These nematodes are soil inhabitants that occur mostly in the vicinity of plant roots. An historical taxonomy, amended diagnosis and several taxonomic remarks on the genus are discussed here. A list of all 13 globally known species (and their synonyms) is given and all of them are treated here. For each species, taxonomic information including morphometric data reported worldwide, amended descriptions of females and males, diagnosis of the species and its relationships with closely related species, as well as its distribution and associated plants are discussed. Moreover, based on the most important morphological and morphometric characters, an identification key and a diagnostic compendium to the species are included. Two populations of T. minor are described and illustrated for the first time from Iran. Comparing morphological and morphometric characteristics of the Iranian populations with other populations worldwide reveals that these populations share almost all diagnostic characters except spear length, which is slightly longer in the Russian populations as compared with populations from USA, Poland and Iran.